2021
DOI: 10.1016/j.xphs.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Inhalation Delivery of Triazavirin in Mice: Outlooks for Advanced Therapy Against Novel Viral Infections

Abstract: Under pandemic-caused emergency, evaluation of the potential of existing antiviral drugs for the treatment of COVID-19 is relevant. Triazavirin, an antiviral drug developed in Russia for per-oral administration, is involved in clinical trials against SARS-CoV-2 coronavirus. This virus has affinity to epithelial cells in respiratory tract, so drug delivery directly in lungs may enhance therapeutic effect and reduce side effects for stomach, liver, kidneys. We elaborated ultrasonic method of triazavirin aerosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Excitingly, seven of them have been reported by medical researchers, such as, triazavirin is a guanine nucleotide analog antiviral that has shown efficacy against influenza A and B, including the H5N1 strain. Given the similarities between SARS-CoV-2 and H5N1, health scientists are investigating triazavirin as an option to combat COVID-19 ( Shahab and Sheikhi, 2021 ) ( Valiulin et al, 2021 ). Aspergillus-producing diseases range from allergic syndromes to chronic lung disease and invasive infections and are frequently observed following COVID-19 infection.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Excitingly, seven of them have been reported by medical researchers, such as, triazavirin is a guanine nucleotide analog antiviral that has shown efficacy against influenza A and B, including the H5N1 strain. Given the similarities between SARS-CoV-2 and H5N1, health scientists are investigating triazavirin as an option to combat COVID-19 ( Shahab and Sheikhi, 2021 ) ( Valiulin et al, 2021 ). Aspergillus-producing diseases range from allergic syndromes to chronic lung disease and invasive infections and are frequently observed following COVID-19 infection.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Valiulin et al ( Valiulin et al, 2021 ) developed the orally available antiviral agent triazavirin in inhaled form and performed the in vivo study on Outbred male mice in an inhalation chamber. The triazavirin aerosol was generated by an ultrasonic nebulizer and the aerosol flowrate in the chamber was maintained at 2.5 L/min by the chamber set-up system.…”
Section: Reformulation Of Anti-sars-cov-2 Agents As Inhalable Formmentioning
confidence: 99%
“…It is in the clinical development phase against SARS-CoV-2 coronavirus. An animal study of triazavirin aerosol inhalation in mice showed 85% bioavailability that is nearly four times higher than that for the traditional per-oral delivery [ 118 ]. The use of intranasal liposomal poly ICLC has been explored for prophylaxis, and treatment as well as a vaccine adjuvant against the highly pathogenic avian influenza A/H5N1 virus [ 119 , 120 ].…”
Section: Inhalation Therapeutics Of Miscellaneous Agents Against Resp...mentioning
confidence: 99%